2001
DOI: 10.1074/jbc.c000831200
|View full text |Cite
|
Sign up to set email alerts
|

Isoprenylcysteine Carboxyl Methyltransferase Deficiency in Mice

Abstract: After isoprenylation, Ras and other CAAX proteins undergo endoproteolytic processing by Rce1 and methylation of the isoprenylcysteine by Icmt (isoprenylcysteine carboxyl methyltransferase). We reported previously that Rce1-deficient mice died during late gestation or soon after birth. We hypothesized that Icmt deficiency might cause a milder phenotype, in part because of reports suggesting the existence of more than one activity for methylating isoprenylated proteins. To address this hypothesis and also to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
124
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 25 publications
3
124
1
3
Order By: Relevance
“…A polyisoprenyl-binding pocket was demonstrated on the Rho dissociation inhibitor [6] that strongly indicates the importance of the farnesyl or geranylgeranyl moiety and indeed of the prenylation pathway changes on protein-protein interactions. Furthermore, a strong influence on physiological well being was demonstrated with mice deficient in isoprenyl carboxylmethyl transferase (PPMTase) which, unable to methylate prenylated protein substrates, did not survive through midgestation [20]. Although this could, in some circumstances, be synonymous with an overactive PMPMEase that would ensure a lower proportion of prenylated and methylated proteins when compared to the unmethylated counterparts, the significance of PMPMEase on the physiological effects of prenylated proteins is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A polyisoprenyl-binding pocket was demonstrated on the Rho dissociation inhibitor [6] that strongly indicates the importance of the farnesyl or geranylgeranyl moiety and indeed of the prenylation pathway changes on protein-protein interactions. Furthermore, a strong influence on physiological well being was demonstrated with mice deficient in isoprenyl carboxylmethyl transferase (PPMTase) which, unable to methylate prenylated protein substrates, did not survive through midgestation [20]. Although this could, in some circumstances, be synonymous with an overactive PMPMEase that would ensure a lower proportion of prenylated and methylated proteins when compared to the unmethylated counterparts, the significance of PMPMEase on the physiological effects of prenylated proteins is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneously immortalized MEFs were prepared from Icmt Ϫ/Ϫ and Rce1 Ϫ/Ϫ embryos, along with control fibroblasts (Icmt ϩ/ϩ and Rce1 ϩ/ϩ ) from littermate embryos (Bergo et al, 2001). The cells were cultured in DMEM with 15% calf serum (Colorado Serum, Denver, CO), nonessential amino acids, 0.1 mM ␤-mercaptoethanol, and l-glutamine in 5% CO 2 at 37°C.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…These studies are therefore uninformative with regard to the specific roles of -AAX proteolysis and carboxyl methylation, both of which require prior prenylation. To investigate these issues, we have inactivated Rce1 and Icmt in the mouse with standard gene-targeting methods (Bergo et al, 2000(Bergo et al, , 2001. Both knockouts were lethal during embryonic development, but we had no difficulty in generating spontaneously immortalized fibroblast cell lines from Rce1 Ϫ/Ϫ and Icmt Ϫ/Ϫ embryos.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Rce1 and Icmt have been recognized for a number of years as potential alternative anticancer targets to FTase. 7 Although originally thought to be too important for cell viability due to the embryonic lethal phenotype of Rce1 −/− and Icmt −/− mice, 8 10 We have therefore initiated an effort to generate Icmt inhibitors based on the structure of the minimal Icmt substrate N-acetyl-S-farnesyl-Lcysteine (AFC, Figure 2, 1) in hopes of developing potent anticancer agents as well as molecular tools to study the structure and mechanism of Icmt.Recently reported work from our laboratories has shown that selective changes in the farnesyl group of AFC can afford effective inhibitors of yeast Icmt ( The biochemical and cellular effects of other FC analogs have been previously reported. Farnesyl thiosalicylic acid (FTS) has been shown to inhibit the growth of H-Ras-driven Rat1 cells, though it is believed this effect is not solely due to inhibition of Icmt.…”
mentioning
confidence: 99%
“…5,6 Rce1 and Icmt have been recognized for a number of years as potential alternative anticancer targets to FTase. 7 Although originally thought to be too important for cell viability due to the embryonic lethal phenotype of Rce1 −/− and Icmt −/− mice, 8 10 We have therefore initiated an effort to generate Icmt inhibitors based on the structure of the minimal Icmt substrate N-acetyl-S-farnesyl-Lcysteine (AFC, Figure 2, 1) in hopes of developing potent anticancer agents as well as molecular tools to study the structure and mechanism of Icmt.…”
mentioning
confidence: 99%